2020
DOI: 10.3389/fpsyt.2020.557160
|View full text |Cite
|
Sign up to set email alerts
|

Impulsivity and Venturesomeness in an Adult ADHD Sample: Relation to Personality, Comorbidity, and Polygenic Risk

Abstract: While impulsivity is a basic feature of attention-deficit/hyperactivity disorder (ADHD), no study explored the effect of different components of the Impulsiveness (Imp) and Venturesomeness (Vent) scale (IV7) on psychiatric comorbidities and an ADHD polygenic risk score (PRS). We used the IV7 self-report scale in an adult ADHD sample of 903 patients, 70% suffering from additional comorbid disorders, and in a subsample of 435 genotyped patients. Venturesomeness, unlike immediate Impulsivity, is not specific to A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…This study showed that impulsive personality traits are genetically associated with substance use and ADHD, suggesting that impulsivity may be an endophenotype contributing to these psychiatric conditions. In line with this notion, a recent study which evaluated the role of impulsivity in ADHD comorbidity, found an adventurous-hyperactive subtype with high genetic load ( Grimm et al, 2020 ). Also, genetic variants associated with cognition phenotypes that are negatively correlated with ADHD may be involved in the susceptibility to SUD (see below).…”
Section: Molecular Geneticsmentioning
confidence: 75%
“…This study showed that impulsive personality traits are genetically associated with substance use and ADHD, suggesting that impulsivity may be an endophenotype contributing to these psychiatric conditions. In line with this notion, a recent study which evaluated the role of impulsivity in ADHD comorbidity, found an adventurous-hyperactive subtype with high genetic load ( Grimm et al, 2020 ). Also, genetic variants associated with cognition phenotypes that are negatively correlated with ADHD may be involved in the susceptibility to SUD (see below).…”
Section: Molecular Geneticsmentioning
confidence: 75%
“…Additionally, it is important to note that ADHD PGS may be differentially associated with various ADHD traits, especially for older adults. For example, Grimm et al (2020) examined ADHD PGS within a sample of 435 adults and found it to be correlated with childhood hyperactivity specifically. They also conducted a principal component analysis and identified three distinct adult ADHD subtypes: impulsive-neurotic, anxious-inattentive, and adventurous-hyperactive; the last of which was the most strongly linked to ADHD PGS.…”
Section: Introductionmentioning
confidence: 99%
“…Animal studies have shown that the selected stimulation of DRD2 receptors with bromocriptine substantially increased the aggressive behaviour of low-aggression genetically modified mice, whereas the blockade of DRD2 receptors with sulpiride decreased or prevented the manifestation of aggressivity in high-aggression genetically modified mice, confirming the critical role of DRD2 receptors in the development of aggressive behaviour [ 12 ]. Taking into account the results of a meta-analysis of 24 genetic studies on aggression reporting that heritability accounts for approximately 50% of the variance in aggression, it is not surprising that genes coding for dopaminergic receptors were largely implicated in the genetic vulnerability for aggressive behaviour and impulsivity in several studies [ 13 , 14 , 15 , 16 , 17 , 18 ]. Both single-nucleotide polymorphisms (SNPs) rs4648317 and rs12364283 in the DRD2 gene ( DRD2 ) were previously associated with impulsive behaviour in a population of healthy volunteers [ 19 ].…”
Section: Introductionmentioning
confidence: 99%